PERSEPSI MAHASISWA MATA KULIAH METODE MENGAJAR KHUSUS TERHADAP SIKAP PERCAYA DIRI MELAKSANAKAN PRAKTIK LAPANGAN KEPENDIDIKAN PRODI PTB FT-UNP - Rizki Vadelha; Revian Body (Universitas Negeri Padang, 2019)
Abstack - Learning Special Teaching Methods (MMK) is one of the factors that determine the success of prospective educators in front of the class, but there needs to be confidence in the learning process. Based on the results of observation by asking questions to students, there are still many prospective educators who are not yet confident in implementing the Educational Field Experience Program (PPLK). The purpose of this study was to determine students' perceptions of self-confidence in implementing the Field Practice of Educational Education in the Building Engineering Education Study Program, Faculty of Engineering, Padang State University. This study is a descriptive study with a total sample population of 73 students. Data collection instruments using a questionnaire with a Likert scale assessment, which consists of 4 answer choices with 37 statements before the validity test and the reliability test, after which there are 29 statements made into research. The results of the study revealed that students' self-confidence in carrying out PPLK was quite sufficient with the results of the Degree of Achievement (DP) of 77.25% in terms of self-confidence, a positive attitude in themselves, and utilizing their strengths. Keywords: Keywords: Special Teaching Methods, Confidence Attitudes, PPLK